Research of the Start-off Slip Friction Control of Hydraulic Torque Converter Lockup Clutch - Xue Dianlun; Chang Neng; Guo Xuekai (Jixie chuandong)
Taking the Lockup clutch in the hydraulic torque converter as the study object,the strategy of start- off slip friction control for the hydraulic torque converter lockup clutch is studied. At first,the dynamics model of lockup clutch and the clutch piston chamber pressure control model are analyzed. Secondly,a new start- off slip friction control strategy is proposed on this basis of the current lockup clutch slip control methods.Next,the clutch hydraulic circuit Simulation X model is established under the strategy of start- off slip friction clutch control. At last,the simulation analysis of the vehicle is carried out. The test results show that the start- off slip friction control strategy of lockup clutch can achieve well in start- off clutch locking processing,the friction time is greatly reduced and the efficiency of the torque converter is improved.